(untitled) (New York, 2007)
The mechanical, optical, and magnetic characteristics of nanomaterials are also presented in detail. Nanomaterials are a fast developing field of research and this book serves as both a reference work for researchers and a textbook for graduate students.
Vật liệu cấu trúc nano
Keywords: Vật liệu cấu trúc nano.,Nanostructured materials.,Hóa nano.,Nanochemistry